How to: Clostridioides difficile infection in children - Krutova, Marcela; de Meij, Tim G J; Fitzpatrick, Fidelma; Drew, Richard J; Wilcox, Mark H; Kuijper, Ed J (Clinical microbiology and infection, 2022)
BACKGROUND: Clostridioides difficile infections (CDI) are traditionally attributed to an older adult patient group but children can also be affected. Although the causative pathogen is the same in both populations, the management of CDI may differ. OBJECTIVES: To discuss the current literature on CDI in the paediatric population and to provide CDI diagnostics and treatment guidance. SOURCES: The literature was drawn from a search of PubMed from January 2017 to July 2021. CONTENT: In the paediatric population, laboratory diagnostics for CDI should preferably be combined with laboratory diagnostics for other gastrointestinal pathogens. Coinfections of CDI are also possible. Though the detection of toxigenic C. difficile using a molecular assay may simply reflect colonisation rather than infection, detection of C. difficile free toxins A/B in faeces is much more indicative of true infection. CDI in children below 2 years of age and in the absence of risk factors is very difficult to diagnose and requires careful clinical judgement pending additional studies. Fidaxomicin has been shown to be superior to vancomycin with a sustained clinical response up to 30 days after the end of CDI treatment in children. Metronidazole is less effective than vancomycin in adults and there are no supporting data for its use in children. In recurrent CDI, treatment should be adjusted according to the drug or drug regimen used for the treatment of a previous episode(s). In multiple recurrent CDI, faecal microbiota transplantation can be effective. IMPLICATIONS: If CDI laboratory testing is indicated in children with diarrhoea, the likelihood of C. difficile colonisation and coinfection with other intestinal pathogens should be considered. The currently available data support a change in the treatment strategy of CDI in children.
Keywords: klostridiové infekce; Child; antibakteriální látky; vankomycin; fidaxomicin; Paediatrics; dítě; Diagnostics; Fidaxomicin; Aged; lidé; Faecal microbiota transplant; Clostridioides difficile; senioři; Anti-Bacterial Agents; Clostridium Infections; Vancomycin; Humans